A Dual-Band Base Station Antenna with a Split Ring for Sub-6 GHz Communication. (9th September 2021) - Huang, Bei; Cao, Jie; Lin, Weifeng; Zhang, Jun; Zhang, Gary; Wu, Fugen
Abstract : A dual-band base station antenna is introduced in this paper. The proposed antenna is composed of baluns, bowtie patches, and a split ring. The two pairs of bowtie patches excited by the two orthogonal balun structures can achieve dual polarization. The split ring is used to yield two additional resonances to broaden the impedance bandwidth. In this way, a compact dual-band base station antenna is obtained with the size of 0.41 λ c × 0.41 λ c × 0.13 λ c ( λ c is the wavelength in the free space at the lowest operating frequency band) and the average gain of 8.2 dBi. Moreover, the operating frequency bands of the proposed antenna cover 2515–2675 MHz, 3400–3600 MHz, and 4800–5000 MHz, which can function as an element for macro- or microcells in sub-6 GHz communications.